Optimisation of momelotinib with improved potency and efficacy as pan-JAK inhibitor. (15th June 2022) - Desai, Jigar; Patel, Bhaumin; Gite, Archana; Panchal, Nandini; Gite, Sanjay; Argade, Anil; Kumar, Jeevan; Sachchidanand, S.; Bandyopadhyay, Debdutta; Ghoshdastidar, Krishnarup; Patel, Hoshang; Chatterjee, Abhijit; et al.
Graphical abstract: Highlights: Inhibition of Janus kinase (JAK) has been identified as promising strategy to treat inflammatory diseases. This paper describes our efforts to discover nanomolar potent JAK kinase inhibitor with excellent pharmacokinetics in rat. We have demonstrated superior animal efficacy data of lead JAK inhibitor in PGPS rat model compared to momelotinib. Abstract: Dysregulated JAK-STAT signaling has been proven to be involved in several immune-mediated diseases. Several janus kinase (JAK) inhibitors have been approved for the treatment of various inflammatory and autoimmune diseases such as rheumatoid arthritis (RA), plaque psoriasis, psoriatic arthritis, inflammatory bowel disease (IBD). Here, we report the design, optimisation, synthesis and biological evaluation of momelotinib analogues (a pyrimidine based JAK inhibitor), to get pan-JAK inhibitors. Systematic structure activity relationship studies led to the discovery of compound 32, which potently inhibited JAK1, JAK2 and JAK3. The in vivo investigation indicated that compound 32 possessed favourable pharmacokinetic properties and displayed superior anti-inflammatory efficacy than momelotinib 1 . Accordingly, compound 32 was advanced into preclinical development.